Association of venous thromboembolism and myocardial infarction with Factor V Leiden and Factor II gene mutations among Libyan patients. Issue 1 (1st January 2021) - Msalati, Abdulghani; Bashein, Abdulla; Ghrew, Murad; Khalil, Ibtesam; Sedaa, Khaled; Ali, Abushawashi; Zaid, Ahmed
ABSTRACT: Factor V Leiden G1691A (FVL) and Factor II prothrombin G20210A (PGM) mutations are the leading causes of thrombophilia. In this study, we have investigated the prevalence of the FVL G1691A and PGM G20210A single nucleotide polymorphisms (SNPs) among Libyan deep vein thrombosis (DVT) and myocardial infarction (MI) patients. SNP genotyping was performed using high-resolution melt analysis (HRM) and DNA sequencing. Biochemical parameters conducted on 112 males and 93 females showed no significant difference in means between the control group and the deep vein thrombosis and myocardial infarction groups. For Factor V Leiden, 40 samples were genotyped. Of the 40 samples, 6 (15.0%) of them were heterozygous and no one was homozygous. As for Factor II SNP, 59 samples were genotyped and only 2 (3.3%) were heterozygous. All the heterozygous samples showed 100% concordance between the HRM-PCR and DNA sequence analysis. Our study showed, for the first time, that both the FVL and PGM mutations are present among Libyan DVT and MI patients and that the FVL mutation is significantly associated with DVT but not with MI. However, our results do not support the association of PGM G20210A mutation with DVT or MI.